Endgame, 1945 : the missing final chapter of World War II - Stafford, David (New York : Little, Brown, 2007)
A narrative chronicle of the three months following VE Day traces the experiences of nine individuals who witnessed the Allied struggle to bring the war to a close, covering such topics as the deaths of Hitler and Mussolini and the liberation of Dachau.
Friday, 20 April 1945 -- 20-30 April 1945 (Himmler's bid, Boulevard of broken dreams, Alpine refuge) -- Hitler's death to VE Day: Dealing with the Nazis, The Cap Arcona, the end of Hitler's Reich, Hitler's loot -- VE Day to Potsdam: Iron Curtain, Berlin, Monday, 16 July 1945, Other beasts in other lairs.
Includes Index
Keywords: World War, -- 1939-1945; Nineteen forty-five, A.D.